2010
DOI: 10.1007/s00775-010-0631-4
|View full text |Cite
|
Sign up to set email alerts
|

Platination of telomeric DNA by cisplatin disrupts recognition by TRF2 and TRF1

Abstract: Telomeres, the nucleoprotein complexes located at the ends of chromosomes, are involved in chromosome protection and genome stability. Telomeric repeat binding factor 1 (TRF1) and telomeric repeat binding factor 2 (TRF2) are the two telomeric proteins that bind to duplex telomeric DNA through interactions between their C-terminal domain and several guanines of the telomeric tract. Since the antitumour drug cisplatin binds preferentially to two adjacent guanines, we have investigated whether cisplatin adducts c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Moreover, we confirmed this result by UV melting temperature experiments. Since cisplatin GG adducts were known to affect the melting temperature of duplex oligonucleotides [ 54 ], we purified the cisplatin-GG adducts formed on the telomeric sequence (TTAGGG) 4 by gel electrophoresis, as previously described [ 44 ], and determined the UV melting temperature of its duplex form compared to the one of the non-modified duplex ( Figure S1b ). As expected, the presence of a cisplatin DNA-adduct reduces the melting temperature from 56 to 42 °C and, importantly, these conditions remain fully compatible with the telomere purification procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we confirmed this result by UV melting temperature experiments. Since cisplatin GG adducts were known to affect the melting temperature of duplex oligonucleotides [ 54 ], we purified the cisplatin-GG adducts formed on the telomeric sequence (TTAGGG) 4 by gel electrophoresis, as previously described [ 44 ], and determined the UV melting temperature of its duplex form compared to the one of the non-modified duplex ( Figure S1b ). As expected, the presence of a cisplatin DNA-adduct reduces the melting temperature from 56 to 42 °C and, importantly, these conditions remain fully compatible with the telomere purification procedure.…”
Section: Resultsmentioning
confidence: 99%
“…The following data from the literature support this hypothesis. Unquestionably, in vitro studies have shown that cisplatin, a well-known chemotherapeutic agent that cross-links adjacent guanines [GG] in duplex DNA [ 39 ], binds efficiently to telomeric DNA with a two to three fold preference relative to genomic DNA, in accordance with the higher probability of finding adjacent guanines in telomeric DNA [ 40 , 41 , 42 , 43 ], and prevents TRF2 binding to telomeric DNA in vitro [ 44 ]. Moreover, a few studies have investigated the cellular effects of cisplatin [ 45 ] on telomeres, pointing out a possible interaction of this drug with telomeric DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The role of negative regulation of telomere terminus of TRF1 is mainly dependent on telomerase; its main function is to promote the T-loop formation located at telomere terminus. According to its role, TRF1 overexpression will shorten the telomere terminus length, thus contributing to tumor cells abnormal proliferation [ 14 16 ]. TRF2 does not depend on telomerase; the main role is to prevent telomere terminus fusion and maintain the genetic information and telomeres structure stable [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ten picomoles of Alu and telomeric (T 2 AG 3 ) 3 probes were end labeled with 10 pmol of [␥-32 P]ATP (PerkinElmer) and purified using G-25 columns (GE Healthcare). Quantitation of telomere binding was done using the formula (telo IP/telo input)/(Alu IP/Alu input) (25), and values are expressed relative to WT telomerase binding to telomeres.…”
Section: Methodsmentioning
confidence: 99%